Imaging of choroid plexus infection by Stomatococcus mucilaginosus in neutropenic patients. - Guermazi, A; Miaux, Y; Laval-Jeantet, M (American Journal of Neuroradiology, 1995)
We report two neutropenic patients with Stomatococcus mucilaginosus meningitis and choroid plexus involvement on neuroimaging studies. CT and MR showed abnormal enlargement of the choroid plexus in one lateral ventricle and intense enhancement. In one patient there was edema in the periventricular white matter adjacent to the involved choroid plexus; in both patients there was enhancement of the ependyma.